Mn content optimum on microstructures and mechanical behavior of Fe-based medium entropy alloys. (November 2022) - Zhao, Yanchun; Ma, Huwen; Zhang, Linhao; Zhang, Dong; Kou, Shengzhong; Wang, Bo; Li, Wensheng; Liaw, Peter K.
Graphical abstract: Highlights: The Medium entropy alloys possess low stacking fault energy and unique high as cast dislocation densities. The modified Warren-Averbach equation and the thermodynamic model are used to calculate alloy dislocation density and stacking fault. Low stacking fault energy and high mixing enthalpy improve storage capacity of dislocation density, promote formation of ε-martensites, and improve strength and plasticity. Optimizing Mn content and coordinating the balance between stacking fault energy and the mixing enthalpy, can regulate optimal dislocation density. Abstract: Fe-XMn-5Si-10Cr-0.9C (X = 10, 15, 20, and 25 wt%) medium entropy alloys (MEAs) with different Mn contents were prepared by magnetic suspension melting in a water-cooled copper crucible, and casted in a negative pressure suction copper mould. The modified Warren–Averbach equation and the thermodynamic model were used to calculate the alloy dislocation density and stacking faults, respectively. The effects of the Mn content on the phase structure, stacking fault energy (SFE), dislocation density, and mechanical properties of the alloy were investigated. The results indicate that the MEAs possess a low stacking fault energy (∼8.50–14.44 mJ/m 2 ) and a unique high as-cast dislocation density (up to 4.8 × 10 15 m −2 ). The microstructure of the as-cast alloys consisted of austenite phase. As loading, the γ → ε martensite transformation occurs and is accompanied by obvious work-hardening behaviour. A low SFE and high ΔSmix improved the storage capacity of the dislocation density, promoted the formation of ε-martensite, and improve the strength and plasticity. Both the SFE and ΔSmix increased with an increase in the Mn content, and the dislocation density initially increased and then decreased. Optimising the Mn content and coordinating the balance between the SFE and ΔSmix can regulate the optimal dislocation density.